The Importance of English Language in Tourism Sector: A Study in Socotra Island - AL-Ragdhi, Ahmed; AL-Rakbi, Abdulhamid; AL-Ragdhi, Khaled; Bin-Hady, Wagdi (Journal of Language Learning and Assessment, 2024)
Purpose This study aims to highlight the significance of English language proficiency for sustainable tourism development on Socotra Island. It explores the impact of enhancing English language skills among professionals in the tourism sector and local residents. Methodology The study utilizes a quantitative research approach, with a close-ended survey shared with 27 professionals in the tourism industry on the island.". Results/Findings Results of the study revealed that tourist guides place great importance on mastering the English language in developing tourism on Socotra Island, M= 4.14. Furthermore, the results showed a high level of recognition among tourist guides that improving English proficiency could lead to economic opportunities for the local population and contribute to the growth of the tourism sector in Socotra, M= 4.05. Implications The results emphasize the urgent need to enhance English language skills to promote positive interactions between tourists and locals, provide economic opportunities for residents, and contribute to sustainable development in the tourism industry on Socotra Island. This study contributes to the existing literature by emphasizing the strategic importance of English language proficiency for sustainable tourism development on Socotra Island.